Spectra of plasmon-exciton composite under weak coherent pumping within cavity QED treatment. (10th January 2020) - Lu, Yu-Wei; Li, Ling-Yan; You, Chun-Lian; Liu, Jing-Feng
Abstract: The quantum states of plasmon-exciton polariton are generally revealed through its scattering spectra in experiments. Here, we present the exact quantum-electrodynamics results of the spectra of plasmon-exciton composite, considering the multimode features of the plasmonic cavity. Different from a single-mode cavity, we find that the existence of higher-order modes leads to incoherent plasmon-exciton coupling, which saturates the cooperativity as the dipole moment of the quantum emitter (QE) increases. Furthermore, the competition of the coherent and incoherent coupling yields an optimal dipole moment for maximum spectral splitting. Though the higher-order modes are nonradiative, they modify the local dynamics of the QE, which present in the scattering spectra through the interplay between the dipolar plasmonic mode and the QE. We demonstrate that the scattering spectra are dominant by the cavity radiation and essentially different from the spontaneous emission (SE) spectrum. However, we show that the photoluminescence spectra of the QE coincide with its SE spectrum, which is a more reliable way to demonstrate the vacuum Rabi splitting.